2019
DOI: 10.3389/fmicb.2019.00921
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of the BID Domain: Conserved Function as Type-IV-Secretion-Signal and Secondarily Evolved Effector Functions Within Bartonella-Infected Host Cells

Abstract: Bartonella spp. are facultative intracellular pathogens that infect a wide range of mammalian hosts including humans. In order to subvert cellular functions and the innate immune response of their hosts, these pathogens utilize a VirB/VirD4 type-IV-secretion (T4S) system to translocate Bartonella effector proteins (Beps) into host cells. Crucial for this process is the Bep intracellular delivery (BID) domain that together with a C-terminal stretch of positively charged residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Christoph Dehio addressed the functional versatility of the Bartonella VirB/D4 T4SS Bep substrates. The effectors are composed of only three basic domain types that are highly versatile in function, allowing them to adapt their original function to host cell subversion, by post‐translation modification of target proteins, for example, AMPylation by FIC domains, interfering with signalling pathways mimicking eukaryotic protein pY motifs, and so forth (Wagner, Tittes, & Dehio, ). Another fine example of host cell subversion by a T4SS effector was reported by Maria Lucas (University of Cantabria, Spain), who showed that the effector RavN of the L. pneumophila Dot/Icm T4SS mimics host cell E3 ligases to exploit the ubiquitylation pathway (Lin et al, ).…”
Section: Effector‐mediated Subversion Of Host Cellsmentioning
confidence: 99%
“…Christoph Dehio addressed the functional versatility of the Bartonella VirB/D4 T4SS Bep substrates. The effectors are composed of only three basic domain types that are highly versatile in function, allowing them to adapt their original function to host cell subversion, by post‐translation modification of target proteins, for example, AMPylation by FIC domains, interfering with signalling pathways mimicking eukaryotic protein pY motifs, and so forth (Wagner, Tittes, & Dehio, ). Another fine example of host cell subversion by a T4SS effector was reported by Maria Lucas (University of Cantabria, Spain), who showed that the effector RavN of the L. pneumophila Dot/Icm T4SS mimics host cell E3 ligases to exploit the ubiquitylation pathway (Lin et al, ).…”
Section: Effector‐mediated Subversion Of Host Cellsmentioning
confidence: 99%
“…The bartonellae utilize a VirB/VirD4 T4SS to translocate a cocktail of B artonella e ffector p roteins (Beps) into host cells, and their orchestrated activities modulate multiple cellular processes and thereby decisively contribute to the stealth infection strategy and capacity of these pathogens to cause chronic infection [6, 7]. Beps are multi-domain proteins that share a common architecture at their C-terminus, which is composed of a ‘ B ep intracellular d elivery’ (BID) domain and a positively charged tail that together constitute an evolutionary conserved bipartite signal for T4SS-mediated translocation [8, 9]. Despite their conserved fold [10], BID domains display significant variability in surface-exposed amino acids that facilitated the evolution of specific, non-enzymatic effector functions within host cells, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Small GTPases of the Ras-protein superfamily are molecular switches that control fundamental cellular functions in eukaryotes by cycling between GTP-bound "on" and GDP-bound "off" conformational states of their switch regions 1 (Sw1) and 2 (Sw2) (Didsbury et al, 1989;Wennerberg et al, 2005). Members of the Ras-homology (Rho) protein family function as signaling hubs and regulate cytoskeletal rearrangements, cell motility, and the production of reactive oxygen species (Heasman and Ridley, 2008;Jaffe and Hall, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial genus Bartonella comprises a rapidly expanding number of virtually omnipresent pathogens adapted to mammals, many of which have been recognized to cause disease in humans (Wagner and Dehio, 2019). The stealth infection strategy of Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation